The Effect of Using Song Vocabulary to Students’ Retention - Rifka Nurin Nafisah; Albadri Albadri; Musdalifah Musdalifah (JOEY: Journal of English Ibrahimy, 2026)
This study determines the effect of using song vocabulary to students’ retention. This research was conducted at the grade Intermediate in Syu’batul Lugha Al-Khairiyah, Ma’hadul Qur’an, Sukorejo, Situbondo. This research used a quantitative method by using Pre-Experimental research type one group pretest posttest design. This research used saturated sampling technique, which a whole of population which consists 19 students are sample. The instrument data collection used test. Data analysis technique using analysis of t-test by paired sample t-test. It was gotten t0 = (-19.396) > tt = (2,861) with sig. (2-tailed) value was 0,000. So, it meant that H0 is refused and Ha is accepted.